Impact of prior treatment on patients with relapsed multiple myeloma treated with carfilzomib and dexamethasone vs bortezomib and dexamethasone in the phase 3 ENDEAVOR study - Moreau, P (NATURE PUBLISHING GROUP, 2022)
10.1038/leu.2016.186